2020
DOI: 10.1038/s41598-020-60219-8
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive fitness of Sapindus emarginatus Vahl populations towards future climatic regimes and the limiting factors of its distribution

Abstract: Sapindus emarginatus Vahl (Sapindaceae) also known as 'Indian Soap nut' is significantly important for saponin content in its fruits. However, its current population in India is heavily fragmented due to a lack of sustainable harvesting practices. Moreover, changing climatic regimes may further limit its distribution and possibly compromise the survival of the species in nature. The aim of the present study was to: predict the future distribution range of S. emarginatus; identify the bioclimatic variables limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Based on the genetic structure and geographical variation of Sapindus germplasms, Sun (Sun et al, 2018) found that areas of high altitudes and low minimum temperatures are suitable for the growth of S. delavayi. Ashish Kumar Pal (Pal et al, 2020) found that maximum temperature and annual precipitation were the most critical environmental factors determining the distribution of suitable habitats for S. emarginatus through the MaxEnt model. These ndings also demonstrate that precipitation is a prerequisite for suitable habitat distribution of Sapindus, and that S. emarginatus similarly diverges into signi cantly different ecological suitability.…”
Section: Habitat Distributions Of S Mukorossi S Delavayi and S Rarak Under The Current Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the genetic structure and geographical variation of Sapindus germplasms, Sun (Sun et al, 2018) found that areas of high altitudes and low minimum temperatures are suitable for the growth of S. delavayi. Ashish Kumar Pal (Pal et al, 2020) found that maximum temperature and annual precipitation were the most critical environmental factors determining the distribution of suitable habitats for S. emarginatus through the MaxEnt model. These ndings also demonstrate that precipitation is a prerequisite for suitable habitat distribution of Sapindus, and that S. emarginatus similarly diverges into signi cantly different ecological suitability.…”
Section: Habitat Distributions Of S Mukorossi S Delavayi and S Rarak Under The Current Environmentmentioning
confidence: 99%
“…Zhang et al (Zhang, Jing, Li, Liu, & Fang, 2019) and Peng et al (Peng et al, 2019) explored suitable habitats for Cinnamomum camphora and Paeonia ostia under current and future climate conditions, respectively, using ecological niche models and offered suggestions for their respective targeted collection and preservation. Ashish (Pal, Vaishnav, Meena, Pandey, & Singh, 2020) also simulated the adaptability and limiting factors of Sapindus emarginatus Vahl in the face of future climate regimes through two ecological niche models. Therefore, ecological niche model appear one of the optimal solutions to establishing how species will adapt to future climate scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, S. mukorossi saponins have outstanding market benefits. India exports approximately 63,368 kg of saponin extract every year, and the total global saponin trade value is expected to reach US$970 million in 2023 (Kumar Pal et al 2020). With the reduction of petroleum reserves, biodiesel will become the main substitute for nonrenewable fossil fuels globally (Chakraborty and Baruah 2013), and the S. mukorossi biomass energy industry is also gradually developing.…”
Section: Introductionmentioning
confidence: 99%